OLIGARCHIZATION AS A CRISIS SYNDROME OF MODERNIZATION OF INDEPENDENT UKRAINE - Пояркова, Т. К. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
A process of oligarchization of Ukrainian political system as a logical consequence of «perestroika» – the last attempt of modernization is reviewed in this article. Main characteristics of this process are singled out: power concentration within the family circle, dependence of political system upon the geopolitical environment. Here it is determined, that the condition for survival of oligarchical authorities is the existence of symbiotic «Soviet-neofeudal» methods: business permits and state aids for ruling circle, and at the same time increase of power control over socium, which, by its own, stipulate the disfunctionality of political system.